Atherosclerotic alterations in human carotid observed by scanning electron microscopy - Dell’Orbo, Carlo; Quacci, Daniela; Raspanti, Mario; Congiu, Terenzio; Reguzzoni, Marcella; Protasoni, Marina (Italian Journal of Anatomy and Embryology, 2010)
Atherosclerosis involves all the layers of the artery wall, but the events involving the intimal portion are fundamental to understand the evolution and gravity of lesions. This study shows that scanning microscopy is instrumental for better understanding the physiopathology of this disease.